0865 Beta-hydroxybutyrate infusion affects glucose metabolism before and after parturition in dairy cows. (1st October 2016) - Zarrin, M.; Grossen-Rösti, L.; Bruckmaier, R. M.; Gross, J. J.
Abstract: Recent studies in mid- and late-lactating dairy cows showed that β-hydroxybutyrate (BHBA) infusion had considerable impact on glucose metabolism and immune response during intramammary lipopolysaccharide challenge. The objective of the present study was to infuse BHBA during the dry period and after parturition to investigate the effects of elevated plasma BHBA concentrations on metabolism and endocrine changes in transition dairy cows. Eight multiparous Holstein cows in wk −2 (a.p.) and wk +2 (p.p.) relative to calving were infused (from 0800 AM to 1200 AM, 4 h) with a BHBA solution to increase plasma BHBA concentrations to 1.5 to 2.0 mmol/L (HyperB). The same period on the next day (without any infusion) was assigned as the control (Control). Blood samples were taken before the start of infusion as reference samples, and every 30 min during the following 6 h (4 h infusion and 2 h after the stop of infusion) in HyperB and on the control day, and were analyzed for glucose, BHBA, insulin, and glucagon. Plasma BHBA concentrations reached 1.7 ± 0.1 mmol/L (a.p.), and 1.6 ± 0.2 mmol/L (p.p.) in HyperB compared with 0.6 ± 0.1 mmol/L, and 0.6 ± 0.0 mmol/L in Control, respectively. The 4-h average BHBA infusion rate was 12.4 ± 1.0 and 13.3 ± 0.9 µmol/kg BW/min in wk −2 and +2, respectively ( P = 0.13). BHBA infusion caused a decrease of plasma glucose concentrations, compared with pre-infusion levels, both before and after parturition ( P < 0.05). The glucose response did not differ between a.p. and p.p. infusion even though basal glucose concentrations were different before and after calving (3.7 ± 0.1 vs. 3.2 ± 0.2 mmol/L, P < 0.05). BHBA infusion increased plasma insulin a.p. but not p.p. ( P < 0.05) despite greater basal insulin concentrations before compared with after parturition (29.0 ± 8.4 vs. 5.8 ± 0.8 µU/mL, P < 0.05). Though basal glucagon concentrations were not different between wk −2 and +2 ( P = 0.30), BHBA infusion decreased plasma glucagon only p.p. ( P < 0.05). These findings show that effects of hyperketonemia on plasma glucose concentrations are independent of lactational stage, but endocrine adaptation to hyperketonemia differs before and after parturition. It can be assumed that BHBA has a glucose sparing effect and is a metabolic key regulator in early lactating dairy cows.